3D modeling of keloid scars in vitro by cell and tissue engineering - Dutsadee Suttho (2018)
ï¿½ 2016, Springer-Verlag Berlin Heidelberg. Keloids are pathologic scars defined as dermal fibrotic tumors resulting from a disturbance of skin wound healing process. Treatments against keloids are multiple, sometimes empirical and none of them really provides an effective tool for physicians. The lack of effective treatments is correlated with the poor understanding of keloid pathogenesis. To fill this gap, researchers need strong models mimicking keloids as closely as possible. The objective of this study was to establish in vitro a new reconstructed keloid model (RKM), by combining fibroblasts extracted from the three major area of a keloid (center, periphery, non-lesional) in a three-dimensional biomaterial. To this aim, fibroblasts of three keloid locations were extracted and characterized, and then integrated in a hydrated collagen gel matrix during a three-step procedure. The heterogeneity of fibroblasts was assessed according to their proliferative and remodeling capacities. RKMs were further visualized and characterized by both light and scanning electron microscopy. This reconstructed keloid model should be very useful for investigating keloid fibroblasts function in conditions mimicking in vivo situation. Moreover, RKM should also be a suitable model for either drug study and discovery or innovative approaches using medical devices both during cancer and cancer-like disease investigation.